The effects of preventive shoulder exercises in electromyographic and pain levels in child swimming athletes - A before-after analysis - Bona, Renata L. (2023)
The aim of this study was to evaluate maximum voluntary contraction through surface electromyography in stabilizer shoulder muscles, as well as the clinical evaluation of shoulder injury in the pre, post, and detraining stages of specific training in child swimmers. Twelve competitive swimmers volunteered for this study. Anthropometric measurements, clinical examination, electromyography (with Delsys® data acquisition system), and pain intensity levels were performed. Clinical examination and EMG data were compared using repeated-measures ANOVA with Bonferroni correction pre, post, and after detraining. The intervention program lasted for 12 weeks. The pain group presented higher pain intensity values compared to the post-intervention program. Most of the tests presented lower values at the detraining compared to the baseline. After the intervention, pain levels significantly decreased in five tests. Muscle strengthening work is highly recommended because it improves the swimmer's shoulder performance, reducing injuries and decreasing pain intensity after 12 weeks of intervention.